O3 Ex vivo normothermic machine perfusion facilitates gymnotic delivery of RNA interference therapeutics in donor kidneys. (30th July 2021) - Thompson, E R; Sewpaul, A; Figuereido, R; Bates, L; Ferdinand, J R; Connelly, C M; Hosgood, S A; Nicholson, M L; Clatworthy, M R; Ali, S; Wilson, C H; Sheerin, N S
Abstract: Introduction: Normothermic machine perfusion (NMP) of donor kidneys prior to transplantation provides a platform for delivery of novel therapeutics to optimize organ quality. This includes RNA interference (RNAi) therapeutics e.g. antisense oligonucleotides (ASO) that block detrimental microRNAs. The intracellular kinetics of RNAi therapeutics are crucial for their pharmacological effect, however, it remains poorly understood. NMP provides an ideal platform to investigate this further. Method: During NMP, human kidneys (n = 12) were treated for 6 hours with a fluorescently-labelled ASO designed to block microRNA-24-3p activity. Biopsies were taken at 0, 2, 4, and 6 hours. Kidney sections were stained with antibodies against early endosomes (Rab5), late endosomes (Rab7), RNA-induced silencing complexes (GW182) and lysosomes (LAMP2). Confocal microscopy images were obtained and co-localisation quantified using Hugyens™ software following batch deconvolution. The global transcriptomic impact of ASO therapy was also assessed using RNA sequencing. Result: Following 2 hours of NMP, ASO was primarily found in tubular epithelial cells. Co-localisation studies revealed ASO uptake via endocytosis and endosomal sorting occurring during NMP. This was followed by cytoplasmic escape and co-localisation of ASO with GW182 proteins. This pattern of co-localisation was not seen in scrambled sequence or cold perfusion controls. RNAseq analysis revealed a decrease in inflammatory pathways and upregulation of microRNA-24-3p targets. Discussion: This is the first study to demonstrate NMP facilitates gymnotic ASO delivery directly into the RISC, whereby, it blocks microRNA-mediated mRNA silencing and increases bioavailability of protective targets. This study highlights the capacity of NMP to re-programme gene expression in donor kidneys using RNAi therapeutics. Take-home Message: Ex vivo normothermic machine perfusion of donor kidneys provides a unique window of opportunity prior to transplantation when we can deliver therapies to improve the quality of the organ. Novel genetic therapies designed to protect kidneys against ischemia reperfusion injury could potentially increase organ utilisation and improve post-transplant outcomes for the many patients on the kidney transplant waiting list.